Efeito do tratamento térmico nas propriedades eletroquímicas e comportamento de corrosão do aço inoxidável classe 410 em solução de cloreto - Marques, Davi Alves (2021)
Endur 300 alloy is a recently developed stainless steel with low carbon content and microstructure predominantly martensitic, being marketed with a focus application as a structural steel. Endur 300 was obtained through a thermomechanical treatment applied to UNS S41003. Due to the lack of available researches of this alloy in the literature, the objective of this work is to evaluate the electrochemical behavior of the alloy Endur 300 in different NaCl concentrations. The methodology of the work follows the following steps: Preparation of the specimens; electrochemical tests of open circuit potential, linear and cyclic polarization, electrochemical impedance spectroscopy and chronoamperometry, followed by characterization of the surfaces of both alloys before and after corrosion process using Optical Microscopy (OM) and Scanning Electron Microscopy (SEM) and the evaluation by means of microindentation and Vickers hardness test. The results show that the thermomechanical treatment used to obtain the Endur 300 alloy caused microstructural and mechanical changes without significantly altering the corrosion resistance properties. The main corrosion morphology observed for both alloys was localized corrosion, as evidenced by the presence of pits after polarization tests. The effect of increasing the concentration of Clˉ ions resulted in a reduction of the passive film resistance and the pitting potential (Epite). Hardness analysis after 28 days of immersion showed that there was a reduction in the superficial hardness of both alloys. This effect could be more observed for the alloy UNS S41003, which showed a more expressive hardness reduction in all observed media.